ENT 530 Social Media Portfolio: Fifi Collection / Muhamad Afiq Mustaffa - Mustaffa, Muhamad Afiq (2021)
Fifi Collection is a “Sole Proprietorship Business” founded by Muhamad Afiq Bin Mustaffa in early 2020, which provides women’s hijabs and accessories in a variety of colours and design. The idea of creating the business’s name came from the owner where Fifi represents the mix name of owner of the founder and Collections represents that the business is ready to provide hijabs for the customers. The name “Fifi Collection” itself already illustrates that the business will provides hijabs and accessories. The founder, Muhamad Afiq is the agent for Fareha Holdings Sdn Bhd that provides and sells Fareha’s hijab. Most of the hijabs and accessories provided by Fifi Collection are for women in average of 18-40. The price range is determined by the materials and the designs for the hijabs but the price is affordable for everyone to buy.